History and Prevalence of Ulcerative Colitis: A Review - Suraj, Dr Shaini; Patil, Dr Pradeep; Sangolkar, Deepa; Rane, Nayna (International Journal of Innovative Research in Medical Science, 2024)
The first description of ulcerative colitis (UC) dates back to 1859. It is one of the two main types of inflammatory bowel disease. This disease affects the colonic mucosal layer where inflammation causes superficial damage. In the latter part of the 18th century, only the symptoms were recognized but little was known about its cause and treatment. But in 19th century with diagnostic advances, it was known that the disease caused ulcerations in mucosal lining which led to effectiveness in treatment. The early 20th century saw an expansion in understanding of UC and it was differentiated from other gastrointestinal diseases. There was better awareness about the disease pathophysiology and role of immune system. A surge in genetic research and gut microbiome provided the needed information about the causes of the disease. With all this knowledge, there is a definite improvement in quality of life of Ulcerative Colitis patients. This article summarizes the advances in knowledge about ulcerative colitis and its prevalence.